BAHASA INDONESIA BAGI PENUTUR ASING DI VANIMO, PAPUA NUGINI: TINJAUAN EKONOMI - Siswanto NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Jayapura is one of the cities in Indonesia which is directly adjacent to other countries.Besides as the gate of sovereignty of nation, its strategic position also is an entrance forforeign exchange. 70% basic needs of West Sepik Province (Sandaun) located inPapua New Guinea is supplied from the Indonesia border market. This article aimsto discover the motivation of BIPA learners in Vanimo Secondary School and DonBosco Secondary School. This article used qualitative descriptive method. The data wasobtained from questionnaire and interview with the students of BIPA. The result ofthis article indicates a high desire to shop for cheap prices in Indonesia. By masteringIndonesian language, they also able to use bargaining techniques they cannot obtainedthroughout Papua New Guinea. BIPA program in Vanimo is expected to attractstudents to come and shop in Indonesia.